Immunolocalization and Changes of Hydroxyproline-Rich Glycoproteins During Symbiotic Germination of Dendrobium officinale - Li, Yuan-Yuan; Chen, Xiao-Mei; Zhang, Ying; Cho, Yu-Hsiu; Wang, Ai-Rong; Yeung, Edward C.; Zeng, Xu; Guo, Shun-Xing; Lee, Yung-I (Frontiers in Plant Science, 2018)
Hydroxylproline-rich glycoproteins (HRGPs) are abundant cell wall components involved in mycorrhizal symbiosis, but little is known about their function in orchid mycorrhizal association. To gain further insight into the role of HRGPs in orchid symbiosis, the location and function of HRGPs were investigated during symbiotic germination of Dendrobium ofﬁcinale. The presence of JIM11 epitope in developing protocorms was determined using immunodot blots and immunohistochemical staining procedures. Real-time PCR was also employed to verify the expression patterns of genes coding for extensin-like genes selected from the transcriptomic database. The importance of HRGPs in symbiotic germination was further investigated using 3,4-dehydro-L-proline (3,4-DHP), an inhibitor of HRGP biosynthesis. In symbiotic cultures, immunodot blots of JIM11 signals were moderate in mature seeds, and the signals became stronger in swollen embryos. After germination, signal intensities decreased in developing protocorms. In contrast, in asymbiotic cultures, JIM11 signals were much lower as compared with those stages in symbiotic cultures. Immunofluorescence staining enabled the visualization of JIM11 epitope in mature embryo and protocorm cells. Positive signals were initially localized in the larger cells near the basal (suspensor) end of uninfected embryos, marking the future colonization site of fungal hyphae. After one week of inoculation, the basal end of embryos had been colonized, and a strong signal was detected mostly at the mid- and basal regions of the enlarging protocorm. As protocorm development progressed, the signal was concentrated in the colonized cells at the basal end. In colonized cells, signals were present in the walls and intracellularly associated with hyphae and the pelotons. The precise localization of JIM11 epitope is further examined by immunogold labelling. In the colonized cells, gold particles were found mainly in the cell wall and the interfacial matrix near the fungal cell wall. Four extensin-like genes were verified to be highly up-regulated in symbiotically germinated protocorms as compared to asymbiotically germinated ones. The 3,4-DHP treatment inhibited the accumulation of HRGPs and symbiotic seed germination. In these protocorms, fungal hyphae could be found throughout the protocorms. Our results indicate that HRGPs play an important role in symbiotic germination. They can serve as markers for fungal colonization,